SYMPTOMOLOGICAL, CULTURAL AND MOLECULAR VARIABILITY OF ALTERNARIA BRASSICICOLA LEAF SPOT IN BROCCOLI (BRASSICA OLERACEA VAR. ITALICA L.) - GIREESH CHAND; K. K.CHANDRA (International Journal of Pharma and Bio Sciences, 2014)
Variation of Alternaria brassicicola leaf spot of Broccoli (Brassica oleracea var. italica L.) was evaluated based on morphological, cultural and molecular parameters during Rabi season 2010 and 2011. Six isolates of Alternaria were cultured in vitro using different growth medium and the growth pattern of the fungi was studied. Maximum 86 leaf spots were recorded from Naini followed by BHU (74) and minimum 17 spots from CSA samples. The size of spots shown variations in different isolates collected from different places. The leaf spots were followed the reducing trend with the increasing number of spots. The maximum 0.5-1.9mm size of spot was noticed in CSA samples and minimum 0.2-0.7mm from Naini sample. The colour of spots was light olivacious, brown with concentric rings with black pin point at the centre. The conidial length ranged 13-120 µm, width 6-16 µm with 2-8 septa. The growth of A. brassicicola recorded maximum in host extract media followed by Potato Dextrose Agar while the growth observed minimum in Czapek’s medium. The variations also exhibited in protein profiling by using SDS-PAGE. The highest molecular weight of protein was detected in CSA (22kDa) isolates followed by isolates from ND (21kDa) and BHU (21kDa) while minimum 20kDa of protein was recorded in Naini isolate.